Radiometric strategy to track nanopesticides: An important approach to understand the fate, mechanisms of action and toxicity - Takeshita, Vanessa; Munhoz-Garcia, Gustavo Vinícios; Pereira, Anderson Espírito Santo [UNESP]; Tornisielo, Valdemar Luiz; Fraceto, Leonardo Fernandes [UNESP] (Elsevier, 2023)
Nanopesticides are an innovative tool for crop protection, demonstrating the potential to replace conventional pesticides used in agriculture worldwide. Before their commercialization and use, careful evaluation of nanopesticides (environmental fate, toxicity, efficacy, modes of action, and agroecosystem interactions) is required. To ensure the environmental safety of nanopesticides, the standardization of protocols in the evaluation of nanoformulation regulatory aspects is needed. In this sense, we consider that radiometric techniques may be applied in the same way as conventional pesticide regulatory tests. This method can be used to track active ingredients in a biological and environmental system, together with other techniques for characterizing nanomaterials. In this review (1) we share our point of view about the use of radiolabeled pesticides to track nanoformulations in biological and environmental scenarios; and (2) we offer a critical discussion about the advantages and challenges of using radiometric techniques to track these active ingredients associated with nanoformulations.
Keywords: Nanoformulation; Nanotechnology; Radiolabeled pesticide; Regulatory tests